Introduction - Editor-in-Chief (Thai Journal of Rheumatology, 2024)
This third volume of the journal encompasses a wide range of content in the field of Rheumatology, presenting both research studies and diverse case reports, including Assessment of digital health literacy skills among patients, focusing on their ability to independently acquire health-related knowledge using digital technologies. A literature review on the use of Janus Kinase Inhibitors for the treatment of axial spondyloarthritis and psoriatic arthritis, highlighting advancements in managing complex chronic inflammatory diseases. A case report on splenic sarcoidosis, which presents a rare case significant for its implications in the diagnosis and management of patients with persistent fever. A case report on the occurrence of Systemic Lupus Erythematosus following TNF Inhibitor therapy in a patient with Ankylosing Spondylitis, showcasing a complex case of autoimmune disease induced by TNF inhibitors in patients with Ankylosing Spondylitis. A pathology-based quiz on vascular features, specifically designed to evaluate readers’ abilities in analyzing and diagnosing patient symptoms from pathological images. We hope that this volume serves as an essential and valuable resource for healthcare professionals and those interested in the management and treatment of rheumatic and autoimmune diseases.